The Effect of Marital Name Choices on Heterosexual Women's and Men's Perceived Quality as Romantic Partners - Kristin Kelley (Socius: Sociological Research for a Dynamic World, 2023)
Are women and men judged for breaking gender norms in the context of heterosexual marriage? Using the case of marital name choice, the author compared the effect of gender-conventional choices (woman takes man's surname) to gender-egalitarian choices (both partners keep or hyphenate their surnames) on the perceived quality of heterosexual women and men as romantic partners. Relying on a survey experiment ( n0.167em=0.167em501), the author found that U.S. respondents perceived women who kept their surnames and women who shared hyphenated surnames with their husbands to be less committed and loving and to conform less to respondents' image of the ideal wife than women who changed their names. These results show that gender-norm violations, not preferences for a shared spousal surname, explain the marital name penalty. Men in norm-breaking couples were also judged, albeit not as harshly as women, suggesting that there are contexts in which women are granted less gender flexibility than men.
Additional information: The publication of this article was funded by the Open Access Fund of the Leibniz Association and by the WZB Berlin Social Science Center.
Keywords: 300; gender norms; gender inequality; gender flexibility; marital name choices; survey experiment